End of Meeting Report - ISPC 4 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
The fourth ISPC meeting was attended by 26 participants from 14th to 16th September 2011. The report annexes contain the list of participants as well as the final agenda for the meeting.